Promotion of tourist potentials, traffic and investments as the basis of the economic development of Vranjska Banja - Novović Milan; Lukić Aleksandar; Ostojić Bojana; Pećić Milutin (Trendovi u Poslovanju)
Spa tourism has experienced full recognition in international tourist flows in recent decades. This fact points to a significant development opportunity for the Republic of Serbia for more complete utilization of tourist potential in spa towns. One such area is Vranjska Banja in the southeast of Serbia, where the warmest hyperthermal water in the world springs. Apart from therapeutical waters, this tourist spot has preserved tourist values that qualify it to become an ecological oasis in this part of Serbia. Accordingly, the subject of research in the paper is the tourist potential of Vranjska Banja, which has not been sufficiently utilized for the needs of tourism, nor is it sufficiently promoted through digital media. The aim of the work is to identify the impact of tourism on the overall economic development of Vranjska Banja. Qualitative, descriptive, statistical and comparative methods were used in the research. The results show that adequate valorization and promotion of tourist attractions and greater investments in tourism and hospitality activities would lead to faster development of tourism in this area, which would have positive effects on the local economy. The contribution of the work is reflected in the identification of appropriate solutions that can be the basis for formulating the economic development strategy of Vranjska Banja as an ecological destination.